2007
DOI: 10.1359/jbmr.070613
|View full text |Cite
|
Sign up to set email alerts
|

Diphyllin, a Novel and Naturally Potent V-ATPase Inhibitor, Abrogates Acidification of the Osteoclastic Resorption Lacunae and Bone Resorption

Abstract: Dissolution of the inorganic phase of bone by the osteoclasts mediated by V-ATPase and ClC-7 is a prerequisite for bone resorption. Inhibitors of osteoclastic V-ATPase or ClC-7 are novel approaches for inhibition of osteoclastic bone resorption. By testing natural compounds in acidification assays, diphyllin was identified. We characterized diphyllin with respect to the pharmacological effects on osteoclasts.Introduction: Osteoclastic acidification of the resorption lacuna and bone resorption requires activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 55 publications
6
70
0
Order By: Relevance
“…It has also been demonstrated that diphyllin inhibits V-ATPase, and therefore, lysosomal acidification in osteoclasts, which leads to the abrogation of bone resorption (18). The present study suggested that CA inhibits the expression of V-ATPases on A375 cells at concentrations of 0.03, 0.1 or 0.3 µM.…”
Section: Discussionsupporting
confidence: 53%
“…It has also been demonstrated that diphyllin inhibits V-ATPase, and therefore, lysosomal acidification in osteoclasts, which leads to the abrogation of bone resorption (18). The present study suggested that CA inhibits the expression of V-ATPases on A375 cells at concentrations of 0.03, 0.1 or 0.3 µM.…”
Section: Discussionsupporting
confidence: 53%
“…26 In renal principal cells, 4AD interferes with acidification of intracellular vesicles (Figure 4) and leads to inhibition of the PKAdependent phosphorylation of AQP2 at S256, the key trigger for its redistribution to the plasma membrane ( Figure 7B). This effect cannot be explained by global inhibition of PKA because 4AD does not affect total cellular PKA activity ( Figure 6C).…”
Section: Discussionmentioning
confidence: 99%
“…26,49,50 However, because of the vital role of V-ATPases in normal physiology, adverse effects on blocking of V-ATPase may be expected. Hence, it is unclear whether such candidates reach the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRAP activity in cell culture medium was measured as described previously [32]. Briefly, samples were incubated with TRAP reaction buffer, containing p-nitrophenyl phosphate and sodium tartrate, for 1 hour at 37uC in the dark.…”
Section: Measurement Of Trap Activity In Cell Culture Supernatantsmentioning
confidence: 99%